Teenage Childbearing and the Welfare State - Georgi Kocharkov; Jan Mellert; Andra Filote (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Teenage birth rates differ significantly across developed countries. They are higher in countries with high income inequality and low intergenerational income mobility. We develop an economic theory of parental investments and risky sexual behavior of teenagers. The model is calibrated to match the stylized facts about income inequality, intergenerational mobility, and sexual behavior of teenagers in the United States. We then impose Norwegian taxes and education spendings on the baseline model. The Norwegian welfare state institutions go a long way in explaining the differences in teenage birth rates between the United States and Norway.
Keywords: J13; J62; J24; 330